Evidence that the loss of colonic anti-microbial peptides may promote dysbiotic Gram-negative inflammaging-associated bacteria in aging mice - Forsyth, Christopher B.; Shaikh, Maliha; Engen, Phillip A.; Preuss, Fabian; Naqib, Ankur; Palmen, Breanna A.; Green, Stefan J.; Zhang, Lijuan; Bogin, Zlata R.; Lawrence, Kristi; Sharma, Deepak; Swanson, Garth R.; et al. (Frontiers in Aging, 2024)
Aging studies in humans and mice have supported a key role for the intestinal microbiome and an increased abundance of 'inflammaging' Gram-negative (Gn) bacteria.Mechanisms underlying this inflammatory profile in the aging microbiome are unknown. We tested the hypothesis that aging-related decrease in colonic crypt epithelial cell anti-microbial peptides (AMPs) gene expression could promote colonic microbiome inflammatory Gn dysbiosis and inflammaging.Methods. As a model of aging, C57BL/6J mice fecal (colonic) microbiota (16S) and isolated colonic crypt epithelial cells gene expression (RNA-Seq) were assessed at two-month (mth) (human: 18 years-old; yo), 15mth (human: 50yo), and 25mth (human: 84yo). Informatics examined aging-related microbial compositions, differential colonic crypt epithelial cell gene expressions and correlations between colonic bacteria and colonic crypt epithelial cell gene expressions.Results. Fecal microbiota exhibited significant increased relative abundances of proinflammatory Gn bacteria with aging. Colonic crypt epithelial cell gene expression analysis showed significant agerelated down-regulation of key AMPs genes that repress growth of Gn bacteria. Aging-related decrease of AMPs gene expressions significantly correlated with an increased abundances in Gn bacteria (dysbiosis), loss of colonic barrier gene expression, and senescence and inflammation related gene expression.This study supports the proposed model that aging-related loss of colonic crypt epithelial cell AMPs gene expression promotes increased relative abundances of Gn inflammagingassociated bacteria and gene expression markers of colonic inflammaging. These data may support new intestinal gene and microbiome-based targets for aging-related therapies.